Dengue Fever Control and Determinants of Dengue Incidence at Huta Rakyat Public Health Center 2024 - Aldi Munawar Kaloko; Masdalina Pane; Mido Ester Juniati Sitorus; Donal Nababan; Ester Saripati Harianja (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in Indonesia, where it is endemic and frequently leads to outbreaks. Dairi Regency, particularly the Huta Rakyat Public Health Center area, has experienced a marked increase in DHF cases over the past two years. This study aims to analyze the implementation of the dengue control program and identify factors associated with DHF incidence.This research used a sequential explanatory mixed-methods design, beginning with a quantitative phase followed by a qualitative phase to explain and enrich the quantitative findings. The quantitative component employed a cross-sectional survey of 100 respondents, analyzed using logistic regression. The qualitative phase involved 10 in-depth interviews, field observations, and document reviews, with data analyzed through thematic analysis.Quantitative findings indicated that DHF incidence was significantly associated with the waste disposal system (OR = 5.67; 95% CI: 1.773 17.479), attitude (OR = 3.316; 95% CI: 1.032 10.656), and knowledge (OR = 3.057; 95% CI: 1.016 9.198). Poor waste management emerged as the dominant factor, increasing the risk of DHF by 5.67 times. Qualitative findings supported these results, revealing persistent challenges in dengue control, including limited human resources, weak cross-sectoral coordination, irregular community engagement in 3M Plus activities, and a reactive approach that prioritizes fogging only after cases appear. The study recommends strengthening community-based prevention activities, improving waste management through stronger cross-sectoral collaboration, and implementing routine environmental surveillance to inform sustainable intervention planning. These efforts are expected to enhance the effectiveness and long-term sustainability of dengue control in the Huta Rakyat Public Health Center area. Keywords: Dengue Hemorrhagic Fever, Risk Factors, Control, Public Health Center.